Agricultural Plan Programmes of Agricultural Production (Statements) 1965-66 Government of Madras - Planning Commission (Planning Commission, 1964)
The actual Production Statistics compiled by the Director of Statistics, however reveal a total production of 56.12 lakh tonnes during the year 1961-62, i.e., 0.71 lakh tonnes in excess of the original estimate for the year 1961-62. The trend of additional production potential created so far in the Third Plan period no doubt points to the possibility of a slight shortfall in the achievements of the Third Plan target for total food production. It is however estimated that the total level of production could be pushed up to 70-23 lakhs tonnes by the end of 1965-66 if the consumption of chemical fertilisers could be stepped up to 5.83 lakhs tonnes in that year.
Food and Agriculture Department, Government of Madras